Abiotic factors influencing diversity and abundance of congregating fireflies (Coleoptera: Lampyridae) in Miri, Sarawak, Malaysia. (3rd April 2021) - Abdullah, Nur-Athirah; Asri, Lailatul-Nadhirah; Radzi, Siti Nur Fatehah; Musbah, Musa; Hazmi, Izfa Riza; Sulaiman, Norela
ABSTRACT: Records of fireflies are numerous in Peninsular Malaysia and Sabah although little is known regarding the firefly population in Sarawak. Thus, the aim of this study is to document the diversity and abundance of the congregating fireflies and their display trees in Miri, Sarawak, Malaysia and to investigate the possible significance of several abiotic factors in relation to the abundance of fireflies. The study was conducted in February 2019 at Sungai Raan, Sungai Sibuti and Sungai Niah in Sarawak using the sweep net at eleven display trees selected randomly along each river. A total of 296 firefly individuals representing two species, namely Pteroptyx bearni (Olivier 1909) and Pteroptyx malaccae (Gorham, 1880) were recorded. Both species occurred at Sungai Niah with a total of 146 individuals, however, only P. bearni was recorded at Sungai Sibuti (97 individuals) and Sungai Raan (53 individuals). Most fireflies were observed to congregate on the mangrove tree species, Rhizophora apiculata. There was significant negative correlation (r = - 0.164, p<0.05) between the total dissolved solids in the river water and firefly abundance at Sungai Sibuti. However, there were no significant correlations (p>0.05) between the firefly abundance and other abiotic factors at all the study rivers. http://www.zoobank.org/urn:lsid:zoobank.org:pub:A42D2F63-DBB-4376-BAIC-83ABA4A9A537